Determination of galacturonic acid from pomelo pectin in term of galactose by HPAEC with fluorescence detection - Jankana Burana-osot (2018)
Galacturonic acid (GalA) in pomelo pectin was converted to galactose (Gal) by saponification and reduction reaction of carboxy group. The characterization of the product was investigated by1H NMR spectroscopy. The reduced pectin was then hydrolyzed with trifluoroacetic acid (TFA) and analyzed by high-performance anion-exchange chromatography (HPAEC) with fluorescence detector. The content of GalA was calculated from an increased Gal after reaction. The GalA content obtained from this method was higher than that obtained from HPAEC-pulsed amperometric detection (PAD), which affords to analyze GalA directly after hydrolysis. The established method was validated and the results showed good linearity, high precision and high sensitivity. This method could be further applied for the analysis of GalA content in pomelo pectin. © 2010 Elsevier Ltd. All rights reserved.